THE HISTOLOGICAL EVALUATION OF THE EFECTS OF Moringa oleifera LEAF MEAL INCLUSIONS ON THE LIVER AND OVARIES OF FEMALE Oreochromis niloticus - NWANKPA, K. I. (Nigerian Journal of Fisheries, 2016)
The present study was carried out to examine the histological effects of Moringa oleifera leaves as a reproduction inhibitor in controlling the unusual reproduction tendency of female O.niloticus. Thirty- five percent crude protein formulated tilapia feeds of various level of M.oleifera leaf inclusions were fed to 120 females of O.niloticus of average weight of 28.56 +0.46g for 90 days at 4% feeding level of total biomass. The fishes were randomly assigned in triplicates into 12 transparent plastic tanks at a stocking density of 10 fishes per tank. The water quality parameters were monitored weekly throughout the study period. The histological evaluation of the liver and ovaries of O.niloticus fed with 0% Moringa leaf meal (MLM) showed normal liver and ovarian tissue characteristics. In general, it was observed that MLM had alterative effects on the ovaries characteristics. The degree of alterations was directly proportional to the level of MLM inclusion. The histological evaluations showed mild to severe stages of ovarian lamellae deformities, degenerations of oocytes cytoplasm, depletion of yolk particles, oocyte atresia, buckling of oocytes and necrosis. Liquefaction of the nucleus was pronouncedly observed in 10 % and 15% MLM. However, it was observed that MLM only caused vacuolation of the hepatopancrease cells. The alteration of the ovaries’ integrity can be attributed to the abundant phytochemicals inherent in M.oleifera leaves. Therefore, the results obtained from the photomicrographs points clearly that M.oleifera leaves meal can be used to curtail the prolific reproduction of female O.niloticus without affecting its health.